1997
DOI: 10.1542/peds.100.1.e11
|View full text |Cite
|
Sign up to set email alerts
|

Does the Supine Sleeping Position Have Any Adverse Effects on the Child?: I. Health in the First Six Months

Abstract: ABSTRACT. Objective. To assess whether the recommendations that infants sleep supine could have adverse health consequences.Design. A prospective study of infants, delivered before, during, and after the Back to Sleep Campaign in the United Kingdom (UK), followed to 6 months of age. The children were part of the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC).Subjects. Singletons born to mothers resident in the three former Bristol-based health districts of Avon in the period June 1991 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
1
30
1
2
Order By: Relevance
“…In a previous ALSPAC study by Hunt and associates, 11 unadjusted associations were found between sleeping in the prone position and an increased risk of similar symptoms to those we have found here. However, prone sleepers are significantly less likely to use a pacifier and, therefore, any adverse effects we have seen are not attributable to sleeping position.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a previous ALSPAC study by Hunt and associates, 11 unadjusted associations were found between sleeping in the prone position and an increased risk of similar symptoms to those we have found here. However, prone sleepers are significantly less likely to use a pacifier and, therefore, any adverse effects we have seen are not attributable to sleeping position.…”
Section: Discussionsupporting
confidence: 86%
“…The position in which the infant was put to sleep also was investigated, because this has been found to be associated with various health symptoms within the ALSPAC sample. 11 2 Analysis was performed to examine the relationships between the various confounding factors and pacifier use. Logistic regression was used to assess the effects of pacifier use on the health of the study sample at 6 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…A study of infants in England indicated that supine sleeping is not associated with an increase in significant morbidity outcomes, and the risk of respiratory problems was reduced compared with that of prone sleepers. 17 In Asian countries, aspiration is not a problem despite the traditional practice of placing newborns to sleep in the supine position. 18 The review by Malloy 19 of US vital statistics mortality files for the years 1991 to 1996 showed no significant increase in the proportion of postneonatal mortality rate associated with aspiration, asphyxia, or respiratory failure.…”
Section: Commentmentioning
confidence: 99%
“…One showed that eating oily fish during pregnancy was associated with better eye and cognitive development in children 5,6 . Another helped to cement advice that babies should be put to sleep on their backs to reduce the risk of cot death, by showing that this sleeping position did not cause any developmental delays 7 . A third showed the first association between peanut allergy -an emerging epidemic in Western countries -and peanut oil in baby lotions 8 .…”
Section: Childhood and Adolescencementioning
confidence: 99%